2009
DOI: 10.1038/eye.2008.423
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial of intravitreal Avastin vs photodynamic therapy and intravitreal triamcinolone: long-term results

Abstract: Purpose To compare 1-year functional and anatomic outcomes of intravitreal bevacizumab (IVB) and photodynamic therapy plus intravitreal triamcinolone (PDT þ IVTA) combination in patients with neovascular age-related macular degeneration (AMD). Methods In this prospective, randomised, controlled clinical trial, 28 patients were included. All patients were randomised 1 : 1 to 0.04 ml/1 mg of IVB or PDT plus same day 0.1 ml/4 mg IVTA (PDT þ IVTA). Follow-up examinations were performed in monthly intervals in IVB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
0
39
1
1
Order By: Relevance
“…By contrast, the dose of 3.75 mg brought about signiWcant success. For Wnding an optimal dose, we referred to the local application of bevacizumab in Ophthalmology, where doses about 1-2 mg are used successfully for intravitreal injections [17]. As previously mentioned, 100 mg bevacizumab was used in another study in epistaxis in HHT [22,24] and intravenous applications of 5-10 mg per kilogram bevacizumab are described in case reports [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the dose of 3.75 mg brought about signiWcant success. For Wnding an optimal dose, we referred to the local application of bevacizumab in Ophthalmology, where doses about 1-2 mg are used successfully for intravitreal injections [17]. As previously mentioned, 100 mg bevacizumab was used in another study in epistaxis in HHT [22,24] and intravenous applications of 5-10 mg per kilogram bevacizumab are described in case reports [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…colorectal carcinoma, renal cell or breast cancer [15,16]. Bevacizumab is also used intensively and very successfully in ophthalmology for diseases involving neovascularization, such as age-related macular degeneration [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mean BCVA decreased from 0.24 (log-MAR 0.63) to 0.22 (logMAR 0.66), although this was not statistically significant. Numerous studies showed that intravitreal bevacizumab is efficacious in terms of visual acuity and anatomical improvements for the treatment of neovascular AMD [15][16][17][18][19][20]. Costagliola et al [19] report the results of intravitreal bevacizumab injections in 68 treatment-naïve patients with occult CNV.…”
Section: Discussionmentioning
confidence: 97%
“…It was described for use initially systemically as an intravenous treatment (Michels et al 2005) and subsequently via off-label intravitreal administration for AMD (Avery et al 2006;Rich et al 2006). Prospective randomized controlled trials have proven the efficacy of bevacizumab in treating AMD (Sacu et al 2009;Tufail et al 2010), macular edema from CRVO , and diabetic macular edema (DME) in the BOLT trial (Rajendram et al 2012). …”
Section: Rvomentioning
confidence: 99%